Practical biomedical signal analysis using MATLAB - Blinowska-Cieślak, Katarzyna J.; Zygierewicz, J. (Jaroslaw) (Series in medical physics and biomedical engineering., 2022)
"Fully updated and with exclusive new content, this second edition presents a coherent treatment of various signal processing methods and applications. The book not only covers the current techniques of biomedical signal processing, but it also offers guidance on which methods are appropriate for a given task and different types of data"--